2006
DOI: 10.2466/pms.102.3.691-702
|View full text |Cite
|
Sign up to set email alerts
|

Hand and Eye Preference and Their Association with Task Approach by Preschoolers

Abstract: Hand preference, eye preference, and the concordance of hand-eye preference were assessed in 99 healthy preschool-age children (46 boys: Mage= 55.4 mo., SD= 10.5 and 53 girls: Mage=53.6 mo., SD= 11.8). Children were also administered neuropsychological measures requiring attention and reaching to both sides of midline including the Peabody Picture Vocabulary Test, Third Edition, Multiple Boxes Test, Developmental Neuropsychological Assessment Visual Attention, and Imitating Hand Positions. All groups performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(22 reference statements)
1
4
0
1
Order By: Relevance
“…The stability in eye preference tends to increase between 3 and 6 years, and at 6 years, 90% of children have developed some eye preference (Dellatolas, Curt, Dargent-Pare, & De Agostini, 1998;Ozturk et al, 1999). Consistency between hand and eye preferences was found in 68% of preschool-age children, stable across age groups 3-6 years (Mahone, Wodka, & Hiemenz, 2006). This proportion is similar to that found in adults (McManus et al, 1999;Porac & Coren, 1976).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The stability in eye preference tends to increase between 3 and 6 years, and at 6 years, 90% of children have developed some eye preference (Dellatolas, Curt, Dargent-Pare, & De Agostini, 1998;Ozturk et al, 1999). Consistency between hand and eye preferences was found in 68% of preschool-age children, stable across age groups 3-6 years (Mahone, Wodka, & Hiemenz, 2006). This proportion is similar to that found in adults (McManus et al, 1999;Porac & Coren, 1976).…”
Section: Introductionsupporting
confidence: 63%
“…Since these early studies, very little research has been devoted to confirm (or disconfirm) such relationship between reading ability and eye-hand pattern of preference. One recent study showed that crossed handeye preference seems to be ''a benign characteristic'' in relation to tasks requiring attention to both sides of the midline (Mahone et al, 2006). But it can still be heard, from some school teachers in France or in the UK (Beaton, personal communication) at least, that children with discordant eye-hand preference are at risk of difficulties in learning to read.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the outcomes described above, one of the studies included in this review [ 39 ] explored the association between crossed laterality and visual attention. The results showed no relationship between these variables.…”
Section: Resultsmentioning
confidence: 99%
“…Other results. Together with the outcomes described above, one of the studies included in this review [39] explored the association between crossed laterality and visual attention. The results showed no relationship between these variables.…”
Section: Qualitative Analysismentioning
confidence: 99%